Addressing Perceived Racial and Ethnic Disparities in Attorney Discipline - Susan Saab Fortney; Heather Zirke (Washington University Journal of Law and Policy, 2025)
Perceived racial and ethnic disparities in attorney discipline threaten public confidence in the legal profession’s fairness and equity. This Article explores whether lawyers of color are subject to a disproportionate number of disciplinary actions. It draws on studies that reveal patterns of disparate outcomes tied to factors such as practice setting, representation during proceedings, and decision-maker bias. The authors assess how systemic issues may contribute to these disparities and highlights gaps in research and transparency. To address these challenges, the Article recommends a multi-faceted approach. This includes better collection and analysis of demographic data, procedural reforms to ensure equitable treatment, and the adoption of proactive measures to support attorneys most at risk of complaints. These reforms aim to enhance the consistency and impartiality of disciplinary systems while fostering trust and accountability among all stakeholders in the legal profession.
Keywords: AttorneyDisciplineEquity; LegalProfessionDiversity; SystemicBiasReform